Reimagining refuge: a discussion of Serena Parekh’s No Refuge by the author of Justice for People on the Move - Brock, Gillian ca. 20./21. Jh. (Journal of global ethics, 2020)
This article is part of an ‘Author meets author' exchange that focuses on my recent book, Justice for People on the Move, and Serena Parekh’s forthcoming book, No Refuge. I describe some of the ways in which I believe Parekh and I usefully converge on similar recommendations, some of the ways in which we diverge and why there are important matters to discuss as we try to advance the conversation on how to reduce the injustices associated with our international arrangements for dealing with refugees. One point of difference that comes into view is that, because Parekh and I have different foci, the content of the responsibilities for which we advocate sometimes differs significantly. A recommendation which might seem important if we attend only to the plight of refugees might not be optimal if we hope to promote sustainable arrangements that assist as many of the most disadvantaged that surround refugee crises, as well as refugees. Here my broader focus on migration justice and global justice more generally suggest different courses of action should be promoted. Our different agendas sometimes affect the content of our responsibilities here and now.